Un modelo de interacción para la prevención del vih basado en la comunicación sobre sexo entre padres y adolescentes hispanos - Benavides Torres, Raquel Alicia; Bonazzo, Claude; Cruz Quevedo, Juana Edith (University of Texas at Austin, USA, 2007)
Acquired Immunodeficiency Syndrome is a global epidemic. Seventy six percent of the total cases are in the age range of 18-35, which provide suspicions that most of the infections occur during adolescence. Adolescents often engage in sexual risk behaviors because they do not have enough information to make the best decisions concerning their sexual behavior. The adolescents´ parents play a very important role in the sexual development and promotion of HIV/AIDS prevention. Parent-adolescent communication about sex is an important medium for adolescents because it provides them with a source of information and values that allow them to make safer sex decisions. Due to the fact that communication is a bi-directional process, it is important to take into account the parent-adolescent interaction. Therefore, the purpose of this paper is to explain an interaction model for HIV/AIDS prevention based in parent-adolescent communication about sex with the Hispanic population using the Self-Efficacy Theory. The model conceives the parent-adolescent dyad for HIV/AIDS prevention. There are two central elements that support this model. The first is the interaction of parent and adolescent to achieve the same goal, which is HIV/AIDS prevention. The second is focused on the general cultural characteristics of Hispanic families, such as: allocentrism, time orientation, gender roles, and fatalism. The principle concepts in this model are parent-adolescent interactions, preventive behaviors, and HIV/AIDS prevention as an outcome. The parent-adolescent interactions include: cultural characteristics, attitudes, beliefs, and knowledge. Together parent's and adolescent's efficacy expectations may result in the activation of preventive behaviors. The preventive behaviors for adolescents are abstinence, condom use, and partner discussion. The preventive behaviors for parents are quality and quantity of communication about sex. The maintenance and perseverance of parent-adolescent behaviors are regulated by outcome expectations such as, prevention of diseases, perceived benefits, partner protection for the adolescent, closeness and sexual risk reduction for parents. Thus, the adolescent's and parent's belief about the positive results of their behavior should result in the repetition of the preventive behavior. This repetition will increase the probability of preventing HIV/AIDS in Hispanic adolescents. This model illustrates the importance of working with efficacy and outcome expectations to improve the parent-adolescent behaviors for HIV/AIDS prevention. Health care providers may use this model to develop effective prevention programs in the community, guide the development of parent and adolescent skills in an educational context, and modify it to fit other STD's.